Bioequivalence Study of Two Commercial Products of 3mg Dinoprostone Vaginal Tablets - Haleema Yasmin,; Ghazala Ishrat,; Ghousia Saba,; Sohaib Yahya,; Najia Mansoor ,; Mohsin Ali, (Journal of Basic & Applied Sciences, 2018)
A randomized, parallel, active control, in vivo bioequivalence study (with clinical endpoint) determining the bioequivalence of two brands of dinoprostone 3 mg vaginal tablets was conducted in pregnant women at Jinnah Postgraduate Medical Center, Karachi. 3mg Dinoprostone vaginal tablet was administered with a second dose repeated after six hours if clinically prescribed. The bioequivalence was assessed by clinical endpoints and a safety analysis was also conducted for all dosed subjects. Maternal bishop score, CTG and neonatal APGAR score were noted. 90% Confidence Intervals for per protocol population was found well within the ±0.20 range. Test product (Glandin E2) and reference product (prostin E2) were found to be bioequivalent.